1986
DOI: 10.1073/pnas.83.19.7221
|View full text |Cite
|
Sign up to set email alerts
|

Putative diazepam binding inhibitor peptide: cDNA clones from rat.

Abstract: cDNA clones corresponding to the polypeptide that has been shown to be an endogenous diazepam binding inhibitor and may act as a physiological ligand for the benzodiazepine/beta-carboline receptor have been isolated from bacteriophage lambda recombinant libraries from rat hypothalamus, total brain, and liver. The clones contain an open reading frame corresponding to 87 amino acids. A signal sequence is not present. In addition to high levels of mRNA in various brain regions, RNA blot analysis reveals an abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
0
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(71 citation statements)
references
References 38 publications
5
65
0
1
Order By: Relevance
“…This protein factor, which induces an approximately 50-fold decrease in the [Ca 2ϩ ] required to activate m-isozymes, has been identified by amino acid sequence analysis as an acyl-CoA-binding protein (13)(14)(15). Recombinant ACBP obtained from E. coli shows the same molecular and functional properties as the m-calpain activator.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This protein factor, which induces an approximately 50-fold decrease in the [Ca 2ϩ ] required to activate m-isozymes, has been identified by amino acid sequence analysis as an acyl-CoA-binding protein (13)(14)(15). Recombinant ACBP obtained from E. coli shows the same molecular and functional properties as the m-calpain activator.…”
Section: Discussionmentioning
confidence: 98%
“…The primers for PCR were selected externally to the translated sequence of mouse brain cDNA for ACBP (accession number X61431). The sense primer was 5Ј-CTTGATTGCTCCTGCTTCTG-3Ј (nucleotides [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]; the antisense primer was 5Ј-TATGTCCTCACAGGTCACACG-3Ј (complementary to nucleotides 353-373). PCR was carried out by using Amplitaq DNA polymerase and by performing 30 cycles of amplification as described previously (24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid sequence of frog DBI deduced from the corresponding cDNA sequence exhibits 80%o similarity with duck DBI (16,17), whereas the similarity with various mammalian DBI ranged between 61% and 68% (10,(12)(13)(14)(15). Evolutionary pressure has particularly acted to conserve the ODN domain, which interacts with both central and peripheral type benzodiazepine receptors (6,20,29) and which binds acyl-CoA esters (17,30).…”
Section: Discussionmentioning
confidence: 99%
“…The cDNA encoding DBI has been cloned in several mammalian species (12)(13)(14)(15), in birds (16,17), and in yeast (17). Biochemical and immunological studies revealed that DBI-related peptides also occur in the brains of fish (18) and amphibians (19).…”
mentioning
confidence: 99%